Roaming Path Generation Algorithm and Optimization Based On Bezier Curve. Issue 17 (2018) - Li, Jiayao; Sun, Ruizhi; Cheng, Chunming; Li, Sicong
Abstract: Camera roaming plays an extremely important role in constructing various roaming scenarios for virtual systems. However, the existing path (camera) roaming algorithm has the disadvantages of excessive human participation in the roaming path generation process, unpredictable roaming effect, unsmart camera conversion, and mismatched roaming camera and commentary. Therefore, a convenient and automatic path roaming algorithm is proposed. At the same time, the intelligent conversion of the camera is implemented. Based on this, optimization is performed to enable smart matching between the camera and the commentary audio and narration text. First, the key model in the roaming scene is marked to obtain its spatial position; Then the Bessel curve generation principle is studied, and Bessel splines are fitted to the key points according to the mathematical model of the Bezier curve； And then the camera movement is invoked，and the function implements roaming. Finally, the algorithm is optimized to achieve intelligent matching of voice subtitles and pictures. In this way, the automation and intelligence of the roaming path are realized.